'She asked for it' : a textual analysis of the re-negotiation of the meaning of rape in the 1970s-1980s : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University - O'Neill, Jacqueline (Massey University, 2006)
The discursive construction of 'rape' has changed in an important way over the past twenty years. The way we consider and respond to rape today as a society, and often as individuals, is very different to the mid-1970s. 1 Amy Chasteen, "Constructing Rape: Feminism, Change, and Women's Everyday Understandings of Sexual Assault", Sociological Spectrum, vol. 21, issue 2, April, 2001, EBSCOHOST, p. 1. From this period, feminists played a considerable role in the re-negotiation of the meaning of 'rape'. From the narratives of rape victims, feminist discourse produced an alternative meaning. Feminist knowledge and action helped shape legal reform and brought radical changes to the treatment of rape 'victims'. 2 Some people prefer the word 'survivor' to victim as 'victim' carries with it notions of powerlessness and vulnerability. But to speak of a person as a survivor who has only recently experienced such an event seems permature. I use the team 'victim' in this thesis. The focus of this thesis is the shift in the meaning of rape from the mid-1970s to the mid-1980s, and in particular, the role feminists played in it. Meaning is produced in discourse. At any one time particular discourses will be dominant in constructing what is understood to be the 'real' meaning of 'rape'. While the experience of rape is 'real' enough for its victims, how rape is constructed has important implications for the identities and experiences of both rape victims and rapists, and more generally, the experience of all women. Its meaning is, however, always unstable. The discourses that converge to produce dominant meanings are not wholly consistent and at certain times contesting discourses arise. In the 1970s, the meaning of 'rape' became hotly contested. Newer ways of talking and acting, in particular feminist discourse, widened the discursive space for making sense of rape, challenged the constructions which produced the older meaning, and effected a shift in that meaning.
Keywords: Rape; New Zealand